Sistem Perubahan Sosial dan Strategi Perubahan Sosial Sebagai Dasar Inovasi Pembelajaran Agama Islam - Anisyah Rahmadania; Rina Nirwana; Umi Rahmawati; Alfauzan Amin; Mukhlisuddin Mukhlisuddin (Departement of Mathematics Education, 2023)
Thisistudy aimsito describe the system and strategy of socialichange as the basis for innovation in Islamic learning at SMP IT Al Marjan. Theimethod usediin thisistudy is a qualitative description using triangulation analysis. The results of the study state that the changei that occuriin humanilife affect the socialirelations of one human being with another human being. Change has benefits for human survival. Without change, it is certain that there will be no innovation. Change aims to innovate learning so that it doei not becomeistaticibut remains dynamic in facing the times. An educator makes changes with a vision and strategy that is basedion assumptionsiabout futureiconditions thatiare expected toioccur. Only educatorsiwho haveipersonality, behavior, iand theisense ofipower areiable toidealiwith change. iWhen change occurs and society is ready to accept it, then the change will advance life or bring prosperity to its followers, conversely whenichanges occur that are not matched by readiness to accept the change itself, itiwill haveian impaction theiemergence oficonflict, conflictiand lossiof integrity.